Environmental Drivers of Trace Element Variability in Hypnum cupressiforme Hedw.: A Cross-Regional Moss Biomonitoring Study in Georgia and the Republic of Moldova - Omari Chaligava; Inga Zinicovscaia; Liliana Cepoi (Plants)
This study investigates the influence of environmental variables on the elemental composition of Hypnum cupressiforme Hedw. mosses in Georgia and the Republic of Moldova, within moss biomonitoring studies aimed at analyzing atmospheric deposition patterns. Moss samples of Hypnum cupressiforme, characterized by a cosmopolitan distribution and a wide range of habitats, were collected from diverse geographical and climatic zones and analyzed for Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sr, V, and Zn. Statistical methods (Spearman correlations, PCA, Kruskal–Wallis tests) were applied to evaluate interactions between elemental concentrations and factors such as topography, climate, land cover, etc. Results revealed strong correlations among lithogenic elements (Al, Co, Cr, Fe, Ni, and V), indicating natural weathering sources, while Cu exhibited potential anthropogenic origins in the Republic of Moldova. Elevated Cd and Pb levels in Georgian high-altitude regions were linked to wet deposition and steep slopes, whereas Moldovan samples showed higher Sr and Zn concentrations, likely driven by soil erosion in carbonate chernozems. The study highlights geogenic and climatic influences on element accumulation by moss, offering insights into the effectiveness of moss biomonitoring across heterogeneous landscapes.